Plan estratégico para el mejoramiento de la gestión administrativa en la planta procesadora de quesos “Tìo Alejo” de la provincia de Pichincha, cantón Mejía, parroquia Machachi en el período 2014-2017 - Orozco Toapanta, Tania Gissela (2015)
This thesis aims to develop a strategic plan that will look the same organizationally structured to cheese processing plant "Tío Alejo" analyzing the external environment with the help of PEST matrix, the internal environment taking into account all factors that may contribute or directly or indirectly affect the SWOT matrix and designing the processing plant has been developing in the market empirically ignoring key elements such as mission, vision, values, policies and strategies are the same as basic to have the desired success in the local market....